1982
DOI: 10.1128/iai.35.3.1091-1102.1982
|View full text |Cite
|
Sign up to set email alerts
|

Biological and immunological properties of Coxiella burnetii vaccines in C57BL/10ScN endotoxin-nonresponder mice

Abstract: Vaccines prepared from Formalin-killed whole cells of Coxiella burnetii (Ohio strain) or from chloroform-methanol residue (CMR) and extract (CME) of such cells were examined for biological and immunological properties in male C57BL/10ScN endotoxin nonresponder mice. Vaccines containing killed whole cells induced a high incidence of gross pathology, as evidenced by liver necrosis, significant splenomegaly, and significant hepatomegaly in mice. The degree and onset of these pathological changes were directly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…(15) Williams et al (1981) interperitoneally inoculated groups of C57BL/10ScN male mice with 11 different doses of C. burnetii phase I Ohio strain to develop a vaccine against Q fever. (16) All studies reviewed here had endpoint of response as mortality for the test subjects. The dose-response data garnered from these sources are given in Table II. An early study was published in 1956 by Tigertt and Benenson investigating human response to AD strain of C. burnetii.…”
Section: Dose-response Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…(15) Williams et al (1981) interperitoneally inoculated groups of C57BL/10ScN male mice with 11 different doses of C. burnetii phase I Ohio strain to develop a vaccine against Q fever. (16) All studies reviewed here had endpoint of response as mortality for the test subjects. The dose-response data garnered from these sources are given in Table II. An early study was published in 1956 by Tigertt and Benenson investigating human response to AD strain of C. burnetii.…”
Section: Dose-response Data Sourcementioning
confidence: 99%
“…Exposed Intraperitoneally with C. Burnetii (16) The best-fit dose-response model for mortality in peritoneally inoculated C57BL/10ScN mice was the Beta-Poisson model. Statistics of the three model fits to the animal data are summarized in Table V and Table IV.…”
Section: Dose-response Of C57bl/10scn Micementioning
confidence: 99%
“…(1984). It is interesting that Williams & Cantrell (1982) reported that while the residue from chloroform-methanol treated Coxiella burnetii was immunogenic, the extractate had no immunogenic properties. The precise mechanism of the action of chloroform on staphylococcal cell walls is not clear but there is clearly a physico-chemical change following removal of lipids and glycolipids allowing sequential release of antigens from the bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…1984) and an inhibitory factor from mycoplasmas (Nakamura & Itoh 1983); and chloroform-methanol has been used to extract delta-haemolysin from Staph. aureus (Heatley 1971) and protective antigens from Coxiella burnetii (Williams & Cantrell 1982).…”
mentioning
confidence: 99%
“…The protective value of phase I WCV has been well documented (19,28,30,43). Despite the prophylactic efficacy of phase I WCV, we are concerned about the potential for adverse reactions induced by phase I WCV (45). When phase I WCV was first developed and tested, Smadel et al observed local skin reactions, fever, anorexia, and malaise in vaccinated individuals (39).…”
mentioning
confidence: 99%